(3eWGdY GdCfXGQ aj TQM WhGdY GdCfhGQs - (3TeS GdOjf CHh GdKfGA eMehO Hf YHO GdQMef GdCUagGfjs; (3YHO Gddg Hf YeQ Hf eMeO Hf Ydj GdTjQGRj, CHh SYjO CHh GdNjQ fGUQ GdOjf GdHjVGhj,J (B685 (3g` s ((3eMeO Hf WGgQ Hf eGdc Hf GdMGL jhSa s)
(3ChdgG (B:s
(3GdMeO ddg GdPi JhMO HhLhH GdhLhO CeG HYO aEf CQHGH GdYbd eJWGHbhf hCUMGH Gdfbd eJhGabhf hCced GdeYGQa hCfaYgG gh GdYdhe GdTQYjI hdGSjeG Yde CUhd GdOjf , gh CYXegG ehVhYkG s
(3BNQgG (B:s
(3heY Pdc dGfYGOd eG hQO ai efGbHge hMci Yf BKGQge GdeQVjI , hSjQge GdMejO , faYfG Gddg HeMHJge CLeYjf hGdMeO ddg Ydi GdJeGe s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3HChdg agQS ddCHhGH hGdeHGMK cJHg GdSjO CMeO HMQi bfhi SfI (B1257(3g`s
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3JHUQI GdYfhGf (B:s
Keywords: (3GdJhMjO hGdedd hGdfMds